Acoustic Crystallization of 2D Colloidal Crystals - Menath, Johannes; Mohammadi, Reza; Grauer, Jens Christian; Deters, Claudius; Böhm, Maike; Liebchen, Benno; Janssen, Liesbeth M.C.; Löwen, Hartmut; Vogel, Nicolas (Advanced Materials, 2023)
2D colloidal crystallization provides a simple strategy to produce defined nanostructure arrays over macroscopic areas. Regularity and long-range order of such crystals is essential to ensure functionality, but difficult to achieve in self-assembling systems. Here, a simple loudspeaker setup for the acoustic crystallization of 2D colloidal crystals (ACDC) of polystyrene, microgels, and core–shell particles at liquid interfaces is introduced. This setup anneals an interfacial colloidal monolayer and affords an increase in average grain size by almost two orders of magnitude. The order is characterized via the structural color of the colloidal crystal, the acoustic annealing process is optimized via the frequency and the amplitude of the applied sound wave, and its efficiency is rationalized via the surface coverage-dependent interactions within the interfacial colloidal monolayer. Computer simulations show that multiple rearrangement mechanisms at different length scales, from the local motion around voids to grain boundary movements via consecutive particle rotations around common centers, collude to remove defects. The experimentally simple ACDC process, paired with the demonstrated applicability toward complex particle systems, provides access to highly defined nanostructure arrays for a wide range of research communitie
Keywords: structural color; monolayers; self-assembly; colloids; crystallization

A Self‐Ordered Nanostructured Transparent Electrode of High Structural Quality and Corresponding Functional Performance - Döhler, Dirk; Triana Merlo, Andres Dario; Büttner, Pascal; Scheler, Florian; Görlitzer, Eric; Harrer, Johannes; Vasileva, Anna A.; Ali, Ezzeldin; Gruber, Wolfgang; Unruh, Tobias; Manshina, Alina A.; Vogel, Nicolas; et al. (Small, 2021)
The preparation of a highly ordered nanostructured transparent electrode based on a combination of nanosphere lithography and anodization is presented. The size of perfectly ordered pore domains is improved by an order of magnitude with respect to the state of the art. The concomitantly reduced density of defect pores increases the fraction of pores that are in good electrical contact with the underlying transparent conductive substrate. This improvement in structural quality translates directly and linearly into an improved performance of energy conversion devices built from such electrodes in a linear manne
Keywords: nanosphere lithography; anodic alumina; antimony sulfide

Collapse-induced phase transitions in binary interfacial microgel monolayers - Harrer, Johannes; Ciarella, Simone; Rey, Marcel; Loewen, Hartmut; Janssen, Liesbeth M. C.; Vogel, Nicolas (Soft Matter, 2021)
Microgels, consisting of a swollen polymer network, exhibit a more complex self-assembly behavior compared to incompressible colloidal particles, because of their ability to deform at a liquid interface or collapse upon compression. Here, we investigate the collective phase behavior of two-dimensional binary mixtures of microgels confined at the air/water interface. We use stimuli-responsive poly(N-isopropylacrylamide) microgels with different crosslinking densities, and therefore different morphologies at the interface. We find that the minority microgel population introduces lattice defects in the ordered phase of the majority population, which, in contrast to bulk studies, do not heal out by partial deswelling to accommodate in the lattice. We subsequently investigate the interfacial phase behavior of these binary interfacial assemblies under compression. The binary system exhibits three distinct isostructural solid-solid phase transitions, during which the coronae between two small particles collapse first, followed by the collapse between small-large and large-large microgel pairs. A similar hierarchy of phase transitions is found for mixtures of microgels and core-shell particles. Simulations based on augmented potentials qualitatively reproduce the experimentally observed phase transitions. We rationalize the presence of this hierarchy in phase transitions from differences in the interfacial morphology between the species: the larger coronae of softer (and therefore larger) microgels provide a higher resistance to phase transitions compared to the smaller coronae of the more crosslinked microgels and core-shell particles. The control of phase transitions via the molecular architecture further allows the formation of characteristic, flower-like defects by introducing particles with "weaker"coronae that are more prone to collapse with their neighboring particles. Our findings underline the dominating role of the corona for interfacial microgel assemblies, which acts as an energy barrier, shifting the collapse to higher surface pressures. This journal is
CRIS-Team Scopus Importer:2021-05-21

Interface-induced hysteretic volume phase transition of microgels: simulation and experiment - Kolker, Jannis; Harrer, Johannes; Ciarella, Simone; Rey, Marcel; Ickler, Maret; Janssen, Liesbeth M.C.; Vogel, Nicolas; Löwen, Hartmut (Soft Matter, 2021)
Thermo-responsive microgel particles can exhibit a drastic volume shrinkage upon increasing the solvent temperature. Recently we found that the spreading of poly(N-isopropylacrylamide) (PNiPAm) microgels at a liquid interface under the influence of surface tension hinders the temperature-induced volume phase transition. In addition, we observed a hysteresis behavior upon temperature cycling, i.e. a different evolution in microgel size and shape depending on whether the microgel was initially adsorbed to the interface in expanded or collapsed state. Here, we model the volume phase transition of such microgels at an air/water interface by monomer-resolved Brownian dynamics simulations and compare the observed behavior with experiments. We reproduce the experimentally observed hysteresis in the microgel dimensions upon temperature variation. Our simulations did not observe any hysteresis for microgels dispersed in the bulk liquid, suggesting that it results from the distinct interfacial morphology of the microgel adsorbed at the liquid interface. An initially collapsed microgel brought to the interface and subjected to subsequent swelling and collapsing (resp. cooling and heating) will end up in a larger size than it had in the original collapsed state. Further temperature cycling, however, only shows a much reduced hysteresis, in agreement with our experimental observations. We attribute the hysteretic behavior to a kinetically trapped initial collapsed configuration, which relaxes upon expanding in the swollen state. We find a similar behavior for linear PNiPAm chains adsorbed to an interface. Our combined experimental - simulation investigation provides new insights into the volume phase transition of PNiPAm materials adsorbed to liquid interfaces.
CRIS-Team WoS Importer:2021-05-28
Keywords: Responsive microgels; Soft particles; Temperature; Poly(n-isopropylacrylamide); Suspensions; Behavior; Water; Deformation; Adsorption; Dendrimers

Nanogels with tailored hydrophobicity and their behavior at air/water interfaces - Cui, Ruiguang; Ickler, Maret; Menath, Johannes; Vogel, Nicolas; Klinger, Daniel (Soft Matter, 2025)
The interfacial behavior of micro-/nanogels is governed to a large extent by the hydrophobicity of their polymeric network. Prevailing studies to examine this influence mostly rely on external stimuli like temperature or pH to modulate the particle hydrophobicity. Here, a sudden transition between hydrophilic and hydrophobic state prevents systematic and gradual modulation of hydrophobicity. This limits detailed correlations between interfacial behavior and network hydrophobicity. To address this challenge, we introduce a nanogel platform that allows accurate tuning of hydrophobicity on a molecular level. For this, via post-functionalization of active ester- based particles, we prepare poly(N-(2-hydroxypropyl)methacrylamide) (PHPMA) nanogels as a hydrophilic benchmark and introduce gradually varied amounts of hydrophobic propyl or dodecyl moieties to increase the nanogel hydrophobicity. We study the deformation and arrangement of these particles at an air/water interface and correlate the results with quantitative measures for nanogel hydrophobicity. We observe that increasing hydrophobicity of nanogels, either by increasing the hydrophobic moiety ratio or the alkyl chain length, leads to decreased particle deformability and aggregation of an interfacially-adsorbed monolayer. Contrary to what may be intuitively assumed, these changes are not gradual, but rather occur suddenly above a threshold in hydrophobicity. Our study further shows that the effect of hydrophobicity affects the nanogel properties differently in bulk and when adsorbed at liquid interfaces. Thus, this study establishes the transition of interfacial behavior between soft gel-like particles to a solid spherical morphology triggered by the increase in hydrophobicit
Keywords: Benchmarking; Chain length; Microgels; Monolayers; Nanoclay; Nanopores; Active esters; Air/Water Interfaces; External stimulus; Hydrophilic and hydrophobic; Interfacial behaviors; Molecular levels; Nanogels; Particle hydrophobicity; Polymeric networks; Postfunctionalization; Nanogels

Self-assembly of defined core–shell ellipsoidal particles at liquid interfaces - Eatson, Jack; Bauernfeind, Susann; Midvedt, Benjamin; Ciarlo, Antonio; Menath, Johannes; Pesce, Guiseppe; Schofield, Andrew B.; Volpe, Giovanni; Clegg, Paul S.; Vogel, Nicolas; Buzza, D. Martin A.; Rey, Marcel (Journal of Colloid and Interface Science, 2025)
Hypothesis: Ellipsoidal particles confined at liquid interfaces exhibit complex self-assembly due to quadrupolar capillary interactions, favouring either tip-to-tip or side-to-side configurations. However, predicting and controlling which structure forms remains challenging. We hypothesize that introducing a polymer-based soft shell around the particles will modulate these capillary interactions, providing a means to tune the preferred self-assembly configuration based on particle geometry and shell properties. Experiments: We fabricate core–shell ellipsoidal particles with defined aspect ratios and shell thickness through thermo-mechanical stretching. Using interfacial self-assembly experiments, we systematically explore how aspect ratio and shell thickness affect the self-assembly configurations. Monte Carlo simulations and theoretical calculations complement the experiments by mapping the phase diagram of thermodynamically preferred structures as a function of core–shell properties. Findings: Pure ellipsoidal particles without a shell consistently form side-to-side “chain-like” assemblies, regardless of aspect ratio. In contrast, core–shell ellipsoidal particles exhibit a transition from tip-to-tip “flower-like” arrangements to side-to-side structures as aspect ratio increases. The critical aspect ratio for this transition shifts with increasing shell thickness. Our results highlight how we can engineer the self-assembly of anisotropic particles at liquid interfaces by tuning their physicochemical properties such as aspect ratio and shell thickness, allowing the deterministic realization of distinct structural configuration
Keywords: Liquid interfaces; Core-shell polymeric ellipsoidal particles; Capillary interactions; Anisotropic particle; Self-assembly; Phase behaviour

Soft Particles at Liquid Interfaces: From Molecular Particle Architecture to Collective Phase Behavior. - Ciarella, Simone; Rey, Marcel; Harrer, Johannes; Holstein, Nicolas; Ickler, Maret; Löwen, Hartmut; Vogel, Nicolas; Janssen, Liesbeth M. C. (Langmuir, 2021)
-isopropylacrylamide) particle systems using phase-contrast atomic force microscopy and correlate the distinct interfacial morphology with their bulk molecular architecture. We subsequently introduce a new coarse-grained simulation method that uses augmented potentials to translate this interfacial morphology into the resulting phase behavior upon compression. The main novelty of this method is the possibility to efficiently encode multibody interactions, the effects of which are key to distinguishing between heterostructural (anisotropic collapse) and isostructural (isotropic collapse) phase transitions. Our approach allows us to qualitatively resolve existing discrepancies between experiments and simulations. Notably, we demonstrate the first in silico account of the two-dimensional isostructural transition, which is frequently found in experiments but elusive in simulations. In addition, we provide the first experimental demonstration of a heterostructural transition to a chain phase in a single-component system, which has been theoretically predicted decades ago. Overall, our multiscale framework provides a phenomenological bridge between physicochemical soft-particle characteristics at the molecular scale and nanoscale and the collective self-assembly phenomenology at the macroscale, serving as a stepping stone toward an ultimately more quantitative and predictive design approach.

Stimuli-Responsive Behavior of PNiPAm Microgels under Interfacial Confinement - Harrer, Johannes; Rey, Marcel; Ciarella, Simone; Löwen, Hartmut; Janssen, Liesbeth M.C.; Vogel, Nicolas (Langmuir, 2019)
The volume phase transition of microgels is one of the most paradigmatic examples of stimuli-responsiveness, enabling a collapse from a highly swollen microgel state into a densely coiled state by an external stimulus. Although well characterized in bulk, it remains unclear how the phase transition is affected by the presence of a confining interface. Here, we demonstrate that the temperature-induced volume phase transition of poly(N-isopropylacrylamide) microgels, conventionally considered an intrinsic molecular property of the polymer, is in fact largely suppressed when the microgel is adsorbed to an air/liquid interface. We further observe a hysteresis in the core morphology and interfacial pressure between heating and cooling cycles. Our results, supported by molecular dynamics simulations, reveal that the dangling polymer chains of microgel particles, spread at the interface under the influence of surface tension, do not undergo any volume phase transition. The balance in free energy responsible for the volume phase transition is fundamentally altered by interfacial confinement. These results imply that important technological properties of such systems, including the temperature-induced destabilization of emulsions, do not occur via a decrease in the interfacial coverage of the microgels.
CRIS-Team Scopus Importer:2019-08-23

Versatile strategy for homogeneous drying patterns of dispersed particles - Rey, Marcel; Walter, Johannes; Harrer, Johannes; Perez, Carmen Morcillo; Chiera, Salvatore; Nair, Sharanya Sukumar; Ickler, Maret; Fuchs, Alesa; Michaud, Mark; Uttinger, Maximilian; Schofield, Andrew B.; Thijssen, Job H. J.; et al. (Nature Communications, 2022)
After spilling coffee, a tell-tale stain is left by the drying droplet. This universal phenomenon, known as the coffee ring effect, is observed independent of the dispersed material. However, for many technological processes such as coating techniques and ink-jet printing a uniform particle deposition is required and the coffee ring effect is a major drawback. Here, we present a simple and versatile strategy to achieve homogeneous drying patterns using surface-modified particle dispersions. High-molecular weight surface-active polymers that physisorb onto the particle surfaces provide enhanced steric stabilization and prevent accumulation and pinning at the droplet edge. In addition, in the absence of free polymer in the dispersion, the surface modification strongly enhances the particle adsorption to the air/liquid interface, where they experience a thermal Marangoni backflow towards the apex of the drop, leading to uniform particle deposition after drying. The method is independent of particle shape and applicable to a variety of commercial pigment particles and different dispersion media, demonstrating the practicality of this work for everyday processes.
CRIS-Team WoS Importer:2022-06-10